Enhancing supplier management strategies: integrating purchasing and supplier potential matrices in furniture manufacturing - Susanto, Indhira Prameswari; Pulansari, Farida; Rahmawati, Nur (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
Supplier segmentation is one of the most important supply chain activities for most companies that collaborate with many suppliers such as in furniture manufacturing. Purchasing Portfolio Matrix (PPM) is a segmentation method that considers two dimensions (supply risk and profit impact) which are the basis for classifying materials to be purchased by the company. Supplier Potential Matrix (SPM) is a new supplier segmentation approach that includes two dimensions (capabilities and willingness). These two approaches are important because they have different focuses, namely PPM on suppliers while SPM on relationships. Therefore, the main objective of this research is to classify suppliers using a combination of PPM and SPM and determine the appropriate relationship management strategy. Data collection was carried out in the case of one manufacturing company that works with 74 raw material suppliers. Best Worst Method (BWM) is used to determine the criteria weights in both segmentation approaches. So from the 74 suppliers, the results were 7 suppliers in PPM1, 43 suppliers in PPM2, 5 suppliers in PPM3, and 19 suppliers in PPM4 and different strategies were obtained so that this combined PPM-SPM approach was able to improve supplier management.